Toward a public health of situations: the re-contextualization of risk - Michael W. Ross; João Ferreira-Pinto
This paper reviews the role of situational variables in health risk behaviors and the literature on the impact of context and situation in public health. Three postulates for a situational model are presented: that the situation can account for additional variance in explanation of health risk behaviors; that the power of the situation is reciprocal to the degree of individual autonomy; and that the situation is definable and measurable. A situational presentation methodology is presented for measuring situations in public health with preliminary data on its efficacy in the context of sexual behavior and injecting drug use as HIV transmission risks. Interventions which maximize the use of situationally-based information are discussed. It is concluded that situational presentations may offer additional explanatory power in public health and a means for intervening at a situational level.